Stress, self-esteem and well-being among female health professionals: A randomized clinical trial on the impact of a self-care intervention mediated by the senses. - Eliseth Ribeiro Leão; Daniela Reis Dal Fabbro; Rebeca Barqueiro de Oliveira; Ingrid Ribeiro Dos Santos; Elivane da Silva Victor; Rita Lacerda Aquarone; Cristiane Benvenuto Andrade; Vivian Finotti Ribeiro; Roselaine Coelho de Oliveira; Rosa Friedlander; Daniela Santos Ferreira (PLoS ONE, 2017)
BACKGROUND:Stress levels are evident among health professionals. However, there are few studies on sensory-based self-care aimed at stress management, self-esteem and subjective well-being in this group of professionals. OBJECTIVE:To assess the impact of a self-care intervention mediated by the senses on the stress levels, self-esteem and well-being of health professionals in a hospital environment. METHODS:A total of 93 health professionals participated in an unblinded clinical trial, randomized into four groups: 1) control (no intervention); 2) Monosensory-daily body moisturizing (DBM) with odorless cream; 3) Bisensory-DBM with scented cream; 4) Multisensory-DBM with scented cream associated with audiovisual material. Participants answered specific questionnaires to assess stress, self-esteem and well-being and cortisol samples were collected at baseline, 15 and 30 days following intervention, and at the 30-day follow-up. RESULTS:Self-care was characterized as neglected, with most participants reporting inadequate hours of sleep (74%), irregular physical activity (68%), and inadequate nutrition (45%). Compared to the other groups, the Bisensory group had lower stress on all three assessments (p = 0.017; 0.012; 0.036), a life satisfaction 8% higher at follow-up than at baseline (95% CI: 2% to 15%, p = 0.016), a 10% increase in positive affect (95% CI: 2% to 19%, p = 0.011) and a 12% reduction in negative affect (95% CI: 3% to 21% less, p = 0.014) after 30 days. The Multisensory group showed improvement in self-esteem (p = 0.012) and reduced cortisol (p = 0.036) after 30 days of intervention. The control group showed no changes in the variables studied, except for cortisol: an increase at the 15-day evaluation (denoting higher risk for stress, p = 0.009) and a reduction at follow-up (p = 0.028), which was nevertheless within normal levels. TRIAL REGISTRATION:Clinicaltrials.gov NCT02406755.